Analysis of Copyright Disputes in the Welcome Monument Sketch Case: Between Economic Rights and Obligations of Public Institutions (Case Study of Supreme Court Decision Number 35/Pdt.Sus-Hak Copyright/2020) - Christie, Rachel (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The copyright dispute over the Welcome Monument Sketch between the heirs of the late Henk Nunjung and PT. Grand Indonesia focuses on economic rights related to the use of a logo that resembles a sketch by Henk Nhang without permission. The heirs claim the right to economic compensation because PT. Grand Indonesia used this logo from 2004 to 2020 without approval. Based on Law no. 28 of 2014 concerning Copyright, the moral and economic rights of copyrighted works remain with the creator or his heirs. The court decided that the copyright for the sketch was Henk Nhang's personal property as an artist, not the result of his official relationship as Deputy Governor of DKI Jakarta. As a result of this violation, PT. Grand Indonesia is required to pay compensation of Rp. 16,000,000,000 to the heirs. This case emphasizes the importance of economic rights in protecting copyrighted works from unauthorized exploitation.